Signaling in the elicitation process is mediated through the octadecanoid pathway leading to jasmonic acid. - Mueller, M J (1993)
Fungal cell walls and fragments thereof (elicitors) induce the formation of low and high molecular weight defense compounds in plant cell suspension cultures. This induced synthesis requires a signal molecule transmitting the message between the elicitor plant cell wall receptor and gene activation. We demonstrate in this study that cis-jasmonic acid is rapidly synthesized in plant cell cultures of diverse taxonomic origin (gymnosperms and mono- and dicotyledonous plants) after challenge with a fungal elicitor preparation. The rapid decline of cis-jasmonic acid in some of these tissues is attributed to rapid metabolism of this pentacyclic acid. The induction of alkaloids by several different molecules provoking the elicitation process is strictly correlated with the synthesis of jasmonates. Elicitation leads to a rapid release of alpha-linolenic acid from the lipid pool of the plant cell. alpha-Linolenic acid and 12-oxophytodienoic acid, the formation of which is also induced, are known to be distant precursors of jasmonic acid. We assume cis-jasmonic acid and its precursors to be the signaling molecules in the elicitation process.